THE INFLUENCE OF COMPENSATION AND WORKLOAD ON TURNOVER INTENTION AT PT CITRAMAS MAJUTAMA - Alyaputri, Kania; Udriyah, Udriyah; Pambreni, Yuni (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2024)
Employees with high potential are needed to carry out activities in the company so that company goals can be achieved properly. Loss of qualified employees will cost the organization more time and money in recruiting and training replacements. For this reason, HR management is needed to retain existing individuals. Good HR management helps maintain existing talent in the organization by providing good compensation that can be a deterrent for employees to leave the company. Then, an unbalanced division of labor can result in an excessive workload for employees and potentially increase an employee's intention to turnover. This research uses a quantitative approach. This study aims to measure the significant influence of compensation and workload on turnover intention at PT Citramas Majutama. The results of hypothesis testing and multiple linear analysis show that compensation and workload have a significant influence on turnover intention at PT Citramas Majutama. The coefficient of determination (Adj R2) is 0.532, which indicates that the contribution of the independent variables compensation and workload to the dependent variable turnover intention is 53.2%. In comparison, the remaining 46.8% is influenced by other variables that have not been studied or are not included in the regression in this study.